2018
DOI: 10.6002/ect.2016.0310
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: How smoking history affects kidney allograft outcomes is unclear in the contemporary era of immunosuppression. Here, we examined a broad range of outcomes after kidney transplant, stratifying patients by smoking status documented at time of transplant, in a well-characterized clinical cohort. Results: Overall, 264 kidney allograft recipients (35.5%) had smoking exposure (current or ex-smoker) documented at time of transplant; these were more likely to be white male patients. Patients with versus wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…61 In kidney transplantation, cigarette smoking was associated with decreased graft survival especially smoking at time of tranpslantaion, [62][63][64] hospitalization of infection, and death-censored graft failure. 63,64 However, another study had shown that acute rejection was similar in patients who smokers and non-smokers. 65 Even through some results were non-concordant which it is possible that smoking is a dose-dependent effect which required time to manifest its effects and it had wash-out effect if the period of abstinence is long enough, 56,59,64 smoking is hazardous and should be consider and encourage patients to abstinence.…”
Section: Smoking and Organ Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…61 In kidney transplantation, cigarette smoking was associated with decreased graft survival especially smoking at time of tranpslantaion, [62][63][64] hospitalization of infection, and death-censored graft failure. 63,64 However, another study had shown that acute rejection was similar in patients who smokers and non-smokers. 65 Even through some results were non-concordant which it is possible that smoking is a dose-dependent effect which required time to manifest its effects and it had wash-out effect if the period of abstinence is long enough, 56,59,64 smoking is hazardous and should be consider and encourage patients to abstinence.…”
Section: Smoking and Organ Transplantationmentioning
confidence: 99%
“…58,59 Posttransplant smoking in lung transplant patients was associated with declined of pulmonary function, but the study failed to demonstrate association of cigarette smoke and graft rejection. 61 In kidney transplantation, cigarette smoking was associated with decreased graft survival especially smoking at time of tranpslantaion, [62][63][64] hospitalization of infection, and death-censored graft failure. 63,64 However, another study had shown that acute rejection was similar in patients who smokers and non-smokers.…”
Section: Smoking and Organ Transplantationmentioning
confidence: 99%
“…However, another trial of kidney transplant patients suggests longer periods for smoking cessation [ 24 ]. Kidney allograft recipients who continued to smoke have a higher rate of post-transplant cancer and cardiac events, increased incidence of rejection at one year, and higher risk of death and overall graft failure [ 25 , 26 , 27 ].…”
Section: Preoperative Carementioning
confidence: 99%
“…Some authors recommend the use of e-cigarettes as an aid in quitting smoking. There is not enough evidence to support using e-cigarettes after solid organ transplantation [ 24 , 25 ]. Smokers with a history of more than 30 pack years should have computed tomography as a cancer screening test [ 16 ].…”
Section: Preoperative Carementioning
confidence: 99%